Modelling immune system dynamics: the interaction of HIV and recombinant virus - Jankauskaitė, Ugnė; Štikonienė, Olga (Lietuvos matematikos rinkinys, 2015)
We investigate the dynamical behavior of a mathematical model of HIV and recombinant rabies virus (RV), designed to infect only the lymphocytes previously infected by HIV. This model is described by ﬁve ordinary diﬀerential equations with two discrete delays. The eﬀect of two time delays on stability of the equilibria of the system has been studied. Stability switches and Hopf bifurcations when time delays cross through some critical values are found. Numerical simulations are performed to illustrate the theoretical results.